Automated vehicles : safety of the intended functionality (SOTIF) - Pimentel, Juan R. (SAE International, 2020)
Safety has been ranked as the number one concern for the acceptance and adoption of automated vehicles since safety has driven some of the most complex requirements in the development of self-driving vehicles. Recent fatal accidents involving self-driving vehicles have uncovered issues in the way some automated vehicle companies approach the design, testing, verification, and validation of their products. Safety of the intended functionalitiy (SOTIF) addresses the concept of safety for self-driving vehicles through the inclusion of 10 recent and highly relevent SAE technical papers. Topics that these papers feature include functional safety, SOTIF, and multi-agent safety.
Keywords: Automated guided vehicle systems -- Safety measures.; elektronické knihy; electronic books